1999
DOI: 10.1016/s0925-4773(99)00096-9
|View full text |Cite
|
Sign up to set email alerts
|

The actin cytoskeleton is required for maintenance of posterior pole plasm components in the Drosophila embryo

Abstract: Localization of mRNAs is one of many aspects of cellular organization that requires the cytoskeleton. In Drosophila, microtubules are known to be required for correct localization of developmentally important mRNAs and proteins during oogenesis; however, the role of the actin cytoskeleton in localization is less clear. Furthermore, it is not known whether either of these cytoskeletal systems are necessary for maintenance of RNA localization in the early embryo. We have examined the contribution of the actin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 39 publications
3
28
0
Order By: Relevance
“…Treatment of embryos with the actin-severing drugs Cytochalasin D and Latrunculin A disrupts the localization of oskar mRNA and protein, but not of bicoid mRNA (Lantz et al, 1999), which is similar to what we observed in lasp mutant embryos and consistent with a role of Lasp in actin-…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Treatment of embryos with the actin-severing drugs Cytochalasin D and Latrunculin A disrupts the localization of oskar mRNA and protein, but not of bicoid mRNA (Lantz et al, 1999), which is similar to what we observed in lasp mutant embryos and consistent with a role of Lasp in actin-…”
Section: Discussionsupporting
confidence: 89%
“…oskar mRNA and protein remain tightly associated with the posterior pole during oogenesis and early embryogenesis, in spite of the strong cytoplasmic streaming that occurs after stage 10B of oogenesis (Gutzeit and Koppa, 1982), and experiments with the actin-severing drugs Cytochalasin D and Latrunculin A suggest that oskar mRNA and protein are attached to the actin cytoskeleton (Lantz et al, 1999). In addition, and in contrast to Oskar, Bicoid protein diffuses along the anteroposterior axis after its synthesis and is detected down to 30% of the egg length, although its mRNA is restricted to the anterior pole in the embryo [100-80% egg length (Driever and Nusslein-Volhard, 1988)], which suggests that mRNA localization is not sufficient for protein restriction.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of LKB1 function in germ line clones of presumptive null alleles prevents the reorganization of the oocyte microtubule network at stage 7 that is required for posterior localization of osk mRNA and affects epithelial polarity in the ovarian follicle cells . LKB1 colocalizes with cortical actin in the oocyte, integrity of which is required for anchoring of pole plasm components and nos mRNA (Lantz et al 1999;Forrest and Gavis 2003). It is therefore attractive to speculate that LKB1 might act at the cortex, where actin and microtubule filaments meet, phosphorylating a currently unknown substrate to promote the trapping of pgc-containing RNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Scale bar: 100 µm. The PAR/aPKC complex and phosphoinositide signaling Wheatley et al, 1995;Tetzlaff et al, 1996;Lantz et al, 1999). Mutations in the gene shackleton also show defects in axial expansion and lack pole cells, but the posterior localization of oskar mRNA is normal, indicating that defects in axial expansion alone are sufficient to cause the lack of pole cells (Yohn et al, 2003).…”
Section: Pten Activity Is Required For the Control Of Several Actin Dmentioning
confidence: 99%